Numerical analysis of cold-formed steel open sections under axial compression - Ananthi, G. Beulah Gnana; Knight, G.M. Samuel; Iyer, Nagesh R. (Journal of Structural Engineering, 2024)
This paper presents the numerical investigations of ultimate load capacity prediction and behaviour of cold-formed unlipped single channels with their ends fixed subjected to axial compression using finite element analysis. The numerical study was carried out in the elastic as well as in the range of loading beyond ultimate load. The slenderness ratio of the channels were 40, 80, 100 and 120. Three different web depth with five thickness and three different grades of steel were chosen and totally one hundred and eighty models were conducted. In the present investigation an attempt is made to determine the ultimate load carrying capacity and study the mode of failure. Load verses axial shortening behaviour is studied for slenderness ratio 40 and 120.